Understanding Repurchase Intention in Indonesian Fashion Retail Channels: A Systematic Literature Review - Muhammad Salim; Retno Widowati (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The transformation of the Indonesian fashion retail industry towards an omnichannel system requires a deeper understanding of the factors influencing customer repurchase intention. Among these factors, channel brand image and brand trust play a strategic role in shaping customer loyalty. This study aims to systematically examine the relationship between channel brand image, brand trust, and repurchase intention in Indonesian fashion retail. The research method used is a Systematic Literature Review of scientific articles published between 2015 and 2025 and relevant to the research topic. The results of the study indicate that channel brand image, both offline and online, and brand trust consistently have a positive effect on repurchase intention. In addition, several studies identify customer satisfaction and risk perception as mediating or moderating variables in the relationship between these variables. This study confirms that consistent channel brand image management and strengthening customer trust are key to increasing loyalty and encouraging continuous repurchase in the Indonesian fashion retail industry.